Effects of Distraction on Physiologic Indices and Pain Intensity in children aged 3-6 Undergoing IV Injection - Vosoghi N; - Chehrzad M; Abotalebi Gh; Atrkar Roshan Z (Tehran University of Medical Sciences, 2010)
Background & Objective: Illness, hospitalization and pain are often first crisis children faced with in their early life. Performing painful procedures such as IV injections for medical purposes are inevitable and stressful events in pediatric wards. Distraction is an inexpensive, practical, and nonpharmacological nursing intervention for pain relief. This study aimed to determine the effects of distraction on some physiological indices (heart rate and O2 saturation (and intensity of pain in the hospitalized children aged 3-6 years undergoing IV injection. Methods & Materials: In this clinical trial, 72 children aged 3-6 years who were undergoing IV insertion were recruited for the study. The participants were randomly allocated into two groups of intervention and control. Distraction technique was applied using bubble-maker in the intervention group. After 10 minutes, pain intensity was measured using OUCHER scale. Moreover, heart rate and blood oxygen saturation were measured for three minutes in both groups using Pulse Oxymeter pre- and post-intervention. Results: The findings showed statistically significant differences in the average heart rate (P<0.01) and the amount of saturated oxygen (P<0.009) and the pain intensity (P<0.001) between two groups after the intervention. The pain decreased significantly in the intervention group in comparison with the control group. Conclusion: According to the research findings, distraction with bubble-maker resulted in decreasing the physiological responses and intensity of pain in children aged 3- 6 years. This method can be useful in reliving the pain in preschool children undergoing IV insertion.